Cystic fibrosis-related bone disease: an update on screening, diagnosis, and treatment - Crystal Cobb; Malinda Wu; Vin Tangpricha (Therapeutic Advances in Endocrinology and Metabolism)
Cystic fibrosis-related bone disease (CFBD) is a common endocrinopathy in people living with cystic fibrosis (CF) that is complex and multifactorial in origin. People with CF experience high rates of progressive bone density loss and increased fracture risk. Focus on prevention and treatment of CFBD is of increasing importance in a now aging CF population. This review will discuss current practices in CFBD, gaps in knowledge, and potential future studies with the goal of advancing the clinical care of patients with CFBD.